Solution Combustion Synthesis: Low‐Temperature Processing for p‐Type Cu:NiO Thin Films for Transparent Electronics. Issue 34 (10th July 2017) - Liu, Ao; Zhu, Huihui; Guo, Zidong; Meng, You; Liu, Guoxia; Fortunato, Elvira; Martins, Rodrigo; Shan, Fukai
Abstract : Low‐temperature solution processing opens a new window for the fabrication of oxide semiconductors due to its simple, low cost, and large‐area uniformity. Herein, by using solution combustion synthesis (SCS), p‐type Cu‐doped NiO (Cu:NiO) thin films are fabricated at a temperature lower than 150 °C. The light doping of Cu substitutes the Ni site and disperses the valence band of the NiO matrix, leading to an enhanced p‐type conductivity. Their integration into thin‐film transistors (TFTs) demonstrates typical p‐type semiconducting behavior. The optimized Cu5% NiO TFT exhibits outstanding electrical performance with a hole mobility of 1.5 cm 2 V −1 s −1, a large on/off current ratio of ≈10 4, and clear switching characteristics under dynamic measurements. The employment of a high‐ k ZrO2 gate dielectric enables a low operating voltage (≤2 V) of the TFTs, which is critical for portable and battery‐driven devices. The construction of a light‐emitting‐diode driving circuit demonstrates the high current control capability of the resultant TFTs. The achievement of the low‐temperature‐processed Cu:NiO thin films via SCS not only provides a feasible approach for low‐cost flexible p‐type oxide electronics but also represents a significant step toward the development of complementary metal–oxide semiconductor circuits. Abstract : A solution combustion synthesis is utilized to fabricate p‐type oxide thin‐film transistors (TFTs) at 150 °C. The doping of Cu into the NiO matrix can replace the Ni sites and enhance the p‐type conductivity. The optimized Cu5% NiO TFTs on both Si and ITO (indium tin oxide)/glass with ZrO2 gate dielectrics exhibit an average hole mobility of >1 cm 2 V −1 s −1 and I on / I off of 10 4 .